Identification of High Risk Carotid Artery Stenosis: A Multimodal Vascular and Perfusion Imaging Study - Park, Moo-Seok; Kwon, Soonwook; Lee, Mi Ji; Kim, Keon Ha; Jeon, Pyoung; Park, Yang-Jin; Kim, Dong-Ik; Kim, Young-Wook; Bang, Oh Young; Chung, Chin-Sang; Lee, Kwang Ho; Kim, Gyeong-Moon (Frontiers in Neurology, 2019)
Background: Risk stratification of asymptomatic carotid artery stenosis (ACAS) is still an issue for carotid revascularization. We sought to identify factors associated symptomatic carotid artery stenosis (SCAS) using multimodal imaging techniques. Methods: We retrospectively collected data on patients who underwent carotid artery revascularization. Results from duplex sonography, computerized tomography angiography, brain magnetic resonance imaging, magnetic resonance angiography, perfusion-weighted imaging, and demographic profiles were compared between asymptomatic and symptomatic patients. After propensity matching to remove selection bias, multivariate regression analysis was performed to identify factors associated with symptomatic carotid artery stenosis. We compared the strength of associations between significant imaging factors and symptomatic carotid stenosis using C statistics. Results: A total of 259 patients (asymptomatic 57.1%, symptomatic 42.9%) with carotid stenosis were included. After 1:1 propensity score matching, multivariable analysis revealed that calcification of the plaque [Odds ratio 0.41, 95% confidence interval (CI) 0.182-0.870, p = 0.023], deep white matter hyperintensity (DWMH; Odds ratio 3.46, 95% CI 1.842-6.682, p < 0.001), gradient echo sequences susceptibility vessel sign (Odds ratio 2.35, 95% CI 1.113-5.107, p = 0.027), and increased cerebral blood volume (CBV; Odds ratio 2.17, 95% CI 1.075-4.454, p = 0.032) were associated with SCAS. The combination of these predictors produced an area under the curve of 0.733 (95% CI 0.662-0.803). Conclusions: Absence of plaque calcification, DWMH, gradient echo sequences susceptibility vessel sign, and increased CBV were independent predictors of SCAS. Multimodal imaging may provide information to identify ACAS patients with high risk of ischemic stroke.